2015
DOI: 10.3928/1081597x-20150423-03
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Optical Bench Performance With Clinical Defocus Curves in Varifocal and Trifocal Intraocular Lenses

Abstract: Significant correlations were found between logMAR visual acuity and image quality metric for the multifocal and monofocal IOLs analyzed. This finding enables surgeons to predict visual outcomes from the optical bench analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…Optical bench studies have suggested that the PX IOL might exhibit slightly better overall performance when compared with the FV lens 4,12. A correlation between optical bench image quality and VA has been demonstrated in prior research 13. On balance, results from optical bench studies should be interpreted with caution and carry less weight than prospective comparative clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Optical bench studies have suggested that the PX IOL might exhibit slightly better overall performance when compared with the FV lens 4,12. A correlation between optical bench image quality and VA has been demonstrated in prior research 13. On balance, results from optical bench studies should be interpreted with caution and carry less weight than prospective comparative clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The optical quality of an intraocular lens (IOL) is a key parameter contributing to a patient's visual performance after cataract or refractive surgery, and has drawn the attention of increasing number of researchers in the last years (e.g., [1][2][3][4]). This investigation can help: 1) designers of intraocular lenses, to better estimate the relative effects of modifying an implant design on an average patient's vision, 2) manufacturers, to determine a more accurate control and provide more useful specifications of their ophthalmic products, and 3) surgeons, to better evaluate the implications of specific optical parameters in the IOL selection.…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 3 corneal spherical aberration, 4,5 regular corneal astigmatism, 6,7 corneal irregular astigmatism, 8,9 and effective lens addition. [10][11][12] The literature is full of studies reporting results with several MIOLs according to the standards, [13][14][15][16][17][18][19][20][21][22][23][24] but it is still not clear the influence of biometric factors on the performance of each particular IOL according to the characteristics of the patient. The main aim of this study was to evaluate the performance of a high addition MIOL by means of computing the area under the visual acuity defocus curve 25 and correlate it with several biometric parameters.…”
mentioning
confidence: 99%